Malignant mesenchymoma of the chest wall in an adult. Issue 4 (April 1993) - Jain, S K; Afzal, M; Mathew, M; Ramani, S K
Abstract : Mesenchymoma (hamartoma) of the chest wall is an extremely rare tumour presenting in early infancy or fetal life. Pleural, pulmonary, and lymph node metastases developed in a young man with malignant mesenchymoma of the chest wall. The tumour had several characteristics that differ from the mesenchymoma reported from the other parts of the body.